A Randomized, double-blind, dose ranging clinical trial of intravenous FDY-5301 in acute STEMI patients undergoing primary PCI. (15th January 2022) - Adlam, David; Zarebinski, Maciej; Uren, Neal G.; Ptaszynski, Pawel; Oldroyd, Keith G.; Munir, Shahzad; Zaman, Azfar; Contractor, Hussain; Kiss, Róbert Gábor; Édes, István; Szachniewicz, Joanna; Nagy, Gergely Gyorgy; et al.
Abstract: Background: Ischemia-reperfusion injury remains a major clinical problem in patients with ST-elevation myocardial infarction (STEMI), leading to myocardial damage despite early reperfusion by primary percutaneous coronary intervention (PPCI). There are no effective therapies to limit ischemia-reperfusion injury, which is caused by multiple pathways activated by rapid tissue reoxygenation and the generation of reactive oxygen species (ROS). FDY-5301 contains sodium iodide, a ubiquitous inorganic halide and elemental reducing agent that can act as a catalytic anti-peroxidant. We tested the feasibility, safety and potential utility of FDY-5301 as a treatment to limit ischemia-reperfusion injury, in patients with first-time STEMI undergoing emergency PPCI. Methods: STEMI patients ( n  = 120, median 62 years) presenting within 12 h of chest pain onset were randomized at 20 PPCI centers, in a double blind Phase 2 clinical trial, to receive FDY-5301 (0.5, 1.0 or 2.0 mg/kg) or placebo prior to reperfusion, to evaluate the feasibility endpoints. Participants underwent continuous ECG monitoring for 14 days after PPCI to address pre-specified cardiac arrhythmia safety end points and cardiac magnetic resonance imaging (MRI) at 72 h and at 3 months to assess exploratory efficacy end points. Results: Intravenous FDY-5301 was delivered before re-opening of the infarct-related artery in 97% participants and increased plasma iodide levels ~1000-fold within 2 min. There was no significant increase in the primary safety end point of incidence of cardiac arrhythmias of concern. MRI at 3 months revealed median final infarct sizes in placebo vs. 2.0 mg/kg FDY-5301-treated patients of 14.9% vs. 8.5%, and LV ejection fractions of 53.9% vs. 63.2%, respectively, although the study was not powered to detect statistical significance. In patients receiving FDY-5301, there was a significant reduction in the levels of MPO, MMP2 and NTproBNP after PPCI, but no reduction with placebo. Conclusions: Intravenous FDY-5301, delivered immediately prior to PPCI in acute STEMI, is feasible, safe, and shows potential efficacy. A larger trial is justified to test the effects of FDY-5301 on acute ischemia-reperfusion injury and clinical outcomes. Clinical Trial Registration: CT.gov NCT03470441 ; EudraCT 2017-000047-41 Highlights: This phase 2a trial tested intravenous FDY-5301, containing sodium iodide, to prevent IR injury in heart attack patients FDY-5301 was successfully given within 2 min, before opening the blocked coronary artery FDY-5301 was safe, with no significant adverse events FDY-5301 showed promising trends to reduce heart attack damage This result justify a Phase 3 clinical outcomes trial of FDY-5301 in acute heart attack patients